Effect of Methomyl on the Phenobarbital and Benzo [a] Pyrene Induced Hepatic Microsomal Mixed Function Oxidase System in Rats - Jyotsna A. Patil1, Arun J. Patil1*, Ajit V. Sontakke1, Satish D. Kalme2 and Sanjay P. Govindwar3 (Al Ameen Medical College, 2011)
Methomyl (Lannate) is a pesticide widely used to control of insects in grape gardens. Methomyl treatment induces significant alteration in mixed function oxidase system. The present work was designed to study the inhibitory effect of methomyl on different forms of cytochrome P450 induced by phenobarbital (CYP 2B1, 2B2 and 3A) and benzo[a]pyrene induced (CYP 1A1). Adult male rats were divided into 8 groups of 6 animals each. Microsomes were isolated by calcium precipitation. The levels of electron transport components, CYP 450, cytochrome b5, and cytochrome c-reductase were determined using extinction coefficients. Activities of drug-metabolizing enzymes were assayed. Inducers like phenobarbital, benzo[a]pyrene, showed significant induction of mixed function oxidase in rat. The methomyl treatment (4mg/kg) of inducer-(Phenobarbital, benzop [a] pyrene) pretreated rat caused a significant decrease in electron transport components and activities of drug-metabolizing enzymes when compared with treatment of inducer alone. Induction of mixed function oxidase enzymes due to phenobarbital was also altered by the pretreatment of methomyl. Benzo[a]pyrene treatment of methomyl pretreated rats showed significant decreased levels of electron transport components and drug metabolizing enzymes as compared to benzo[a]pyrene treatment alone. These results indicate that the susceptibility of phenobarbital and benzo[a]pyrene induced cytochrome P450 isoform (CYP 2B1, 2B2, 3A; and CYP 1A1) to methomyl and also affected in the induction pattern of some of the inducers with respect to CYP 450 isoforms.